Virtual Reality Assessment and Customization Using Physiological Measures: A Literature Analysis - Wood, Kody; Uribe Quevedo, Alvaro Joffre; Penuela, Lina; Perera, Sharman; Kapralos, Bill (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
Understanding the user experience requires gathering self-reported and physiological information. In Virtual Reality (VR), heart rate, skin responses, gaze, brain, and muscle activity can provide a better understanding of how users process perceptual cues and respond to them. The purpose of this literature review is to analyze the use of physiological measures in VR customization to identify the state of the art, gaps, and opportunities. A total of 25 articles from indexed journals and top-tier conferences within the last five years were reviewed. The review indicates that the recent availability of consumer-level VR and the growth of ubiquitous physiological sensors are enabling their use for customized and adaptive user experiences.